ANALISIS YURIDIS TENTANG PEDOMAN PELAKSANAAN KREDIT USAHA RAKYAT - Maisa Maisa (Maleo Law Journal, 2018)
In order to realize the welfare of the people that is just and prosperous in accordance with the mandate of the constitution, the government needs to make efforts to meet the needs of people's lives. one form of government policy to meet the needs of the community is the formation and application of the People's Business Credit (KUR) program. Distribution of People's Business Credit (KUR) conducted by the implementing bank accompanied by collateral in the form of land certificates, house certificates or Motorized Vehicle Ownership Books (BPKB), not in accordance with the Coordinating Minister for Economic Affairs Regulation No. 13 of 2015 concerning Guidelines for the Implementation of People's Business Credit which stated that the People's Business Credit without collateral and To overcome the losses suffered by the implementing bank, the government established a KUR credit guarantee policy. 70 (seventy) percent to 80 (eighty) percent charged to state credit guarantee institutions such as PT (Persero) Indonesian Credit Insurance (PT Askrindo) and the Indonesian Credit Guarantee General Company (Perum Jamkrindo) Keyword : Juridical Analiysis. Credit Business.